Pengaruh Fasilitas Kerja dan Beban Kerja Terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sikka - Yuliana Fransiska Bunga; Antonius Philippus Kurniawan; Yustina Olivia Da Silva (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
The background of this research is the achievement of performance that has not yet reached the specified target. This research aimed to (1) determine the description of employee performance, work facilities, and workload; and (2) analyze the effect of work facilities and workload on employee performance both partially and simultaneously. The populations in this research were employees of the Population and Civil Registration Office of Sikka Regency totaling 55 people. This research was conducted by census or saturated sampling. Data were collected through questionnaires and analyzed through descriptive and inferential statistical methods, namely multiple linear regression. Hypothesis testing was done through the F-test and t-test. The results of descriptive analysis showed that the variables of employee performance, work facilities, and workload were categorized as good enough. The results of hypothesis testing showed that partially and simultaneously, the work facility and workload variables had a significant effect on performance. The determination analysis results showed that the two independent variables in this research were able to explain the fluctuation of employee performance at the Population and Civil Registration Office of Sikka Regency by 24.5%.